AC024896.1/miR-363-3p Axis Regulates the Malignant Progression of Acute Myeloid Leukemia by Cuproptosis-Related Gene MYO1B - Zhang J; Zheng Y; Liu H; Liu B (Blood and Lymphatic Cancer: Targets and Therapy, 2024)
Jie Zhang,1 Yuhuan Zheng,1 Hongjuan Liu,2 Bo Liu3 1Department of Blood Transfusion, Ankang Central Hospital, Ankang, Shannxi, 725000, People’s Republic of China; 2Operating Room, Ankang Central Hospital, Ankang, Shannxi, 725000, People’s Republic of China; 3Department of Blood Transfusion, Ankang Hospital of Traditional Chinese Medicine, Ankang, Shannxi, 725000, People’s Republic of ChinaCorrespondence: Bo Liu, Ankang Hospital of Traditional Chinese Medicine, Ankang Municipality of Bashan East Road No. 47, Ankang, Shannxi, 725000, People’s Republic of China, Email 541906839@qq.comBackground: Acute myeloid leukemia (AML) is a hematological malignancy with poor patient prognosis. Cuprotosis is a newly discovered cell death that regulates the proliferation and progression of tumor cells. Long non-coding RNAs (lncRNAs) are key molecules and potential biomarkers for the diagnosis and treatment of various diseases. However, the effect of cuprotosis-associated lncRNAs on AML remains unclear.Objective: The aim of this study was to investigate the relationship between the expression of cuprotosis-related gene and the prognosis of AML.Methods: Consensus cluster analysis was performed on AML patients according to the cuprotosis-related gene expression matrix, and survival analysis and differential gene analysis were performed. Then lncRNA and miRNA related to AML tumor progression were screened according to univariate COX regression analysis. After that, Kaplan-Meier analysis, correlation analysis, and AUC curve were used to determine the ceRNA network that might regulate AML. The regulatory relationship of ceRNA was verified in AML cell lines by RT-qPCR and Western blotting.Results: The AC024896.1/miR-363-3p axis drives MYO1B to promote the malignant progression of AML. First, a change in the expression of AC024896.1 and miR-363-3p can affect the proliferation of AML by regulating MYO1B. Mechanistically, AC024896.1 regulates the expression of MYO1B as the ceRNA of miR-363-3p. Moreover, the regulation of AC024896.1 in the malignant progression of AML depends partly on miR-363-3p.Conclusion: In summary, our study reveals AC024896.1/miR-363-3p/MYO1B Axis in AML, which can be regarded as a new potential target for the diagnosis and treatment of AML.Keywords: acute myeloid leukemia, cuprotosis, ceRNA network, bioinformatics analysis